PENINGKATAN EFEKTIVITAS PRODUKSI TERASI REBON MELALUI SISTEM HYGIEDRY RECTANGULAR DI DESA JEROWARU, LOMBOK TIMUR - Handri Jurya Parmi; Muslihuddin Aini; Lalu Nova Saza Yusma; Junaidi Junaidi (Jurnal Abdi Insani, 2025)
Jerowaru Village is the largest center for rebon shrimp paste production in East Lombok. The traditional sun-drying process, which depends on weather conditions, often hinders production and reduces product quality. In addition, the group’s business management lacks the ability to determine accurate production costs. These issues lead to low efficiency and profitability, thus requiring technological innovation and improved business management capacity. This program aims to improve production effectiveness and business management of the Askia Duta Group through the implementation of the HygieDry Rectangular system, CPPOB training, and Excel-based cost calculation. The methods included program socialization, CPPOB training, cost of goods sold (COGS) training, implementation of the HygieDry Rectangular system, mentoring, and evaluation. Evaluation was carried out using pre- and post-tests and field observations to assess knowledge improvement and production capacity changes. The CPPOB training increased participants’ knowledge scores to 80–100%, while the COGS training achieved similar improvements. The implementation of the HygieDry Rectangular system increased production capacity from 25 kg to 100 kg per batch, accelerated drying by 30%, and produced more hygienic products. The group’s ability to calculate costs and determine selling prices also improved significantly. The program enhanced product quality, reduced production time, and is projected to increase revenue by 20–30% within six months. The program successfully improved production capacity, product quality, and business management skills, strengthening the competitiveness and sustainability of coastal MSMEs.